2022
DOI: 10.1108/intr-06-2022-0407
|View full text |Cite
|
Sign up to set email alerts
|

Online silence: why do people not challenge others when posting misinformation?

Abstract: PurposeThere is a scarcity of research studies on why people remain inactive when encountering and recognising misinformation online. The main aim of this paper is to provide a groundwork for future research into why users do not challenge misinformation on digital platforms by generating hypotheses through a synthesis of pertinent literature, including organisational behaviour, communication, human-computer interaction (HCI), psychology and education.Design/methodology/approachGiven the lack of directly relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…The final theme relates to “combating misinformation” and deals with identifying the limits of individuals' willingness to fight misinformation, also proposing policy interventions to curb the phenomenon. The first paper (Gurgun et al , 2023) explores the motivations behind social media users' “online silence” when encountering misinformation. The author conducts a literature review and identifies six factors (i.e.…”
Section: A Summary Of the Special Issuementioning
confidence: 99%
“…The final theme relates to “combating misinformation” and deals with identifying the limits of individuals' willingness to fight misinformation, also proposing policy interventions to curb the phenomenon. The first paper (Gurgun et al , 2023) explores the motivations behind social media users' “online silence” when encountering misinformation. The author conducts a literature review and identifies six factors (i.e.…”
Section: A Summary Of the Special Issuementioning
confidence: 99%
“…Tone detector (Self-monitoring) Self-monitoring is one of the most popular persuasive strategies [45] and it helps people become more self-aware about their behavioural patterns [46] which also helps them to self-regulate [47]. One potential reason people do not challenge misinformation is that they want to avoid being viewed as aggressive [15]. A tone detector guides users to improve their self-awareness regarding how they sound to others, which would likely be helpful for those who are concerned about how their comments come across.…”
Section: Tunnelingmentioning
confidence: 99%
“…Studies on why people remain silent when they encounter misinformation indicate that users have interpersonal, intrapersonal and institutional concerns such as fear of being harassed, fear of conflict or lack of institutional support [10,14]. Gurgun et al [15] identified six reasons that might impact users' decisions to challenge others who post misinformation: self-oriented, relationship-oriented, others-oriented, content-oriented, individual characteristics, and technical factors. While it is necessary to overcome the barriers that hinder users from challenging misinformation, it is also worthwhile to design social media platforms that are more persuasive and encourage users to challenge misinformation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we derived new items based on the framework developed by Milliken, Morrison and Hewlin [40]. The extensive investigation by Gurgun, Arden-Close, Phalp and Ali [31] about the potential barriers behind people's reluctance to challenge misinformation was the basis for our question items.…”
Section: Barriers To Challenging Misinformationmentioning
confidence: 99%
“…In this paper, we investigate why people avoid or skip challenging misinformation when they notice in the online environment. We assess the extent to which the barriers identified in Gurgun, Arden-Close, Phalp and Ali [31] apply in the context of social media use. We also grouped these barriers into four factors and investigate the influence of demographics on the likelihood to challenge.…”
Section: Introductionmentioning
confidence: 99%